European and world energy perspectives: the 1980s and 1990s - Jochen H. Mohnfeld (Intereconomics, 1982)
Substantial successes have been achieved since 1973 in increasing energy efficiency and substituting other fuels for oil. However, reliance on oil and oil imports remains high. The temporary easing on the oil market must not lead to complacency as any relaxation in energy policy efforts may well contribute to provoking the next oil price shock.
Keywords: 330; Energy